Exploring the Influence of Social Media on English Language Acquisition:: Opportunities and Challenges - Nurhastuti, Devi; Amsa, Helfany; Tabasi, Yosafat; Franchisca, Sherly; Manuhutu, Melda Agnes; Sari, Mike Nurmalia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This research explores the influence of social media on English language acquisition, examining both the opportunities and challenges it presents for learners. With platforms like Instagram, Twitter, and YouTube offering authentic and diverse language exposure, social media has the potential to enhance vocabulary acquisition, cultural understanding, and communicative skills. However, the informal and unregulated nature of these platforms also introduces challenges, such as the risk of internalizing non-standard language forms and the distractions associated with digital media. Through a comprehensive literature review, this study synthesizes existing research to provide insights into the role of social media as a supplementary tool for language learning. The findings reveal that, while social media can support language acquisition, it requires critical engagement and strategic guidance from educators to maximize its benefits and minimize its limitations. This study suggests that, with thoughtful integration into learning frameworks, social media can serve as an effective complement to traditional language learning methods, fostering an engaging and dynamic environment for English language learners.